Congruency of Generation Z Student’s Mathematics Self-Efficacy and Anxiety and Teacher’s Teaching Strategy - Cabonilas, Lister Matos (International Journal on Emerging Mathematics Education, 2024)
This study emphasized the association between generation Z students’ mathematics anxiety and self-efficacy levels and the teaching strategies of mathematics senior high school teachers. The descriptive-correlational method was utilized and researcher-modified questionnaires to gather data of the 50 students. This study employed and utilized mean, standard deviation, z-test and Pearson r. The results showed that (1) the mathematics anxiety level of the students is high and self-efficacy is moderate, (2) the students’ self-efficacy level towards mathematics subject did not significantly affect their anxiety level, (3) senior high school mathematics teachers made use of differentiated instruction and/or strategies but did not significantly affect the anxiety level of the generation Z students, and (4) lecture/discussion, demonstration and project teaching strategies significantly affect the mathematics self-efficacy level of the students. In conclusion, although the generation Z students demonstrate a high mathematics anxiety yet their ability redirect with confidence to exert behaviors basically to produce clear performance accomplishments in mathematics. Finally, the researchers concluded that mathematics anxiety level is not about teacher’s strategy in the class but due to other reasons experienced (past) and developed by the generation Z students and there were conventional teaching strategies (lecture/discussion, demonstration, and project) that can influence mathematics self-efficacy of the students.